Evaluation of the diagnostic performance of ultrasound for clavicle fractures in emergency settings: A meta-analysis and systematic review - Bin Lin; Danqin Yuan; Weiting Chen; Ying Liu; Xiaozhen Ji (Journal of International Medical Research, 2025)
Objective Ultrasound provides real-time, high-resolution imaging and is increasingly recognized as a valuable diagnostic tool for clavicle fractures. Compared with traditional imaging modalities, ultrasound offers advantages such as point-of-care accessibility, absence of radiation exposure, and rapid diagnosis capability, making it particularly useful in emergency settings. However, the diagnostic performance of ultrasound across different clinical studies remains inconsistent. Therefore, this study aimed to systematically assess the diagnostic accuracy of ultrasound for clavicle fractures through a meta-analysis of existing studies. Methods A systematic review and meta-analysis was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. A comprehensive search of PubMed, Scopus, Embase, Cochrane Library, and Web of Science was performed until 25 February 2025. Studies reporting the sensitivity, specificity, and overall diagnostic performance of ultrasound for clavicle fractures were included. Data extraction and statistical analysis were performed using Stata version 18.0. Results A meta-analysis of seven eligible studies showed a pooled sensitivity of 92% (95% confidence interval: 87%–95%) and pooled specificity of 95% (95% confidence interval: 91%–98%), indicating relatively high diagnostic accuracy. Sensitivity showed low-to-moderate heterogeneity, whereas specificity demonstrated significant heterogeneity. Fagan plot and likelihood ratio analysis supported the clinical utility of ultrasound for both confirming and excluding clavicle fractures. The likelihood ratio scattergram indicated that ultrasound shows good performance in ruling in clavicle fractures but only moderately good performance in ruling them out. Conclusion Current evidence indicates that ultrasound is a promising, noninvasive diagnostic modality for clavicle fractures, especially in emergency settings. Its diagnostic accuracy, coupled with its safety profile, makes it a potentially valuable tool. Nevertheless, standardization of scanning protocols and further validation in diverse populations are needed. Future studies are warranted to standardize scanning protocols, evaluate operator-dependent factors, and validate findings across broader clinical settings. Trial registration number: PROSPERO CRD: 42025643069.